PENYUSUNAN PRIORITAS PENGEMBANGAN DESA PESISIR MENURUT PANDANGAN STAKEHOLDER DENGAN MENGGUNAKAN AHP (ANALYTICAL HIERARCHY PROCESS) DI KABUPATEN KULONPROGO - , ICHWAN ARIEF JUNAIDI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Regional Spatial Plan Detail (RDTRK ) South Coast of Kulon Progo Regency has been split several significant land use, such as a special area for the military, agriculture (agricultural wetlands and agricultural land is limited beach), fishing (ocean fisheries and coastal fisheries), tourism, industry, transportation (the plan construction of ports and airports) and settlements. In addition, Local Government Regulation No.2 of 2010 about Spatial Planning (RTRW) also set the iron sand mining. The number of sectors and stakeholders concerned in the management of coastal areas (coastal village) in the absence of integrity in it actually possible conflicts of interest. In the formulation of coastal village development prioritization in Kulon Progo Regency and to minimize conflicts of interest, the AHP (Analytical Hierarchy Process) is the most appropriate tool, because in the AHP to consider all aspects and criteria based on the views of stakeholders (society, government, private sector and NGOs). The purpose of this study was (1) To analyze existing conditions and development plans coastal villages in Kulon Progo Regency (2) To determine the views of stakeholders on the priority direction of development most appropriate for development in coastal villages (3) To preparing guidance coastal village development. The research method used was descriptive-analytic, with quantitative data analysis based on primary and secondary data. The selection of respondents to the AHP was done by purposive sampling or selection with consideration of the respondent intentionally is an actor or land users (stakeholders) is comprised of government, private sector, NGOs and society with the number of respondents for each stakeholder is 10 respondents. AHP questionnaire results were analyzed with the help of software Expert Choiche 2000. The results of this research study is (1) Every coastal village has the characteristics, potential and problems of different regions, based on the existing potential, the development of agriculture is the main priority (2) Based on the AHP according to the combined perceptions of stakeholders was found that the economic aspects of the main priorities developed in order to realize sustainable development of coastal villages. From these results finally obtained results regarding the coastal village development priority order with priority first to the last in a sequence as follows: the development of agricultural areas, tourism, fishery, animal husbandry, transportation, housing, mining and industry, the military. The main priority a coastal village cluster is to develop coastal land farming areas in cluster 1, cluster 2 to the development of marine fishery areas and cluster 3 for agricultural development of wetlands. (3) The concept of management of coastal villages is to focus on the characteristics of the coastal area itself, which is a combination of adaptive development, integrating environmental, economic and social systems.